Comparative Exploration of Motivation, Procrastination, and Academic Achievement among Freshmen, Sophomore And Final Year Students - Lina Natalya; Gabrielle Sinata Sin (Graduate School of Universitas Negeri Malang, 2023)
The objective of this research is to investigate variances in the patterns of the correlation between academic motivation, procrastination, and GPA among students from different universities in Surabaya. This research was conducted using a correlational method involving 1,060 students from four years: 2017, 2018, 2019, and 2020 (n respectively 209, 187, 232, 432). The sampling method was accidental random sampling from February to May 2021. The results showed that GPA, academic motivation, and procrastination fluctuated differently depending on the year of study. The average GPA tends to be high in the first year (µ=3.162) then increases in the second year (µ=3.485) decreases in the third year (µ=3.281) and slightly increases again in the final year (µ=3.309). Academic motivation levels also fluctuated during the four years of study (µ2020=3.849; µ2019=3.735; µ2018=3.917; µ2017=3.808). Meanwhile, procrastination tends to increase from year to year. From the results, it can be concluded that the occurrence of fluctuations in GPA, academic motivation, and procrastination from students is influenced by many factors in the learning process. However, students who can manage their emotions and motivation well tend to have a higher chance of success. Therefore, it is necessary to have the right intervention to help solve their problem of learning.